2004
DOI: 10.1530/eje.0.1510361
|View full text |Cite
|
Sign up to set email alerts
|

Plasma adiponectin and serum advanced glycated end-products increase and plasma lipid concentrations decrease with increasing duration of type 2 diabetes

Abstract: Objective: To prospectively follow the concentrations of plasma adiponectin (p-adiponectin) and serum advanced glycation end-products (s-AGE) in relation to plasma lipids and retinopathy over 3 years in type 2 diabetic patients. Design and methods: P-adiponectin, s-AGE, plasma lipids and diabetic retinopathy were prospectively evaluated in 61 type 2 diabetic patients at baseline and at follow up 3 years later. Results: Mean p-adiponectin (from 8.84^5.14 to 11.05^6.16 mg/ml; P ¼ 0.006) and s-AGE (from 637^242 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
6
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“…Thus, our study seemed to suggest that a preserved endogenous secretion of insulin was of importance for the marked difference in circulating adiponectin levels. In a study of patients with type 2 diabetes examined on two occasions, an association was found between the decline in C‐peptide levels over time and the increase in plasma adiponectin 26 . Although there are many differences between type 1 and type 2 diabetes, including high levels of adiponectin in type 1 diabetes 14–17 and low levels in type 2 diabetes, 8 these results are in agreement with the idea of endogenous insulin secretion modifying adiponectin levels.…”
Section: Discussionmentioning
confidence: 52%
“…Thus, our study seemed to suggest that a preserved endogenous secretion of insulin was of importance for the marked difference in circulating adiponectin levels. In a study of patients with type 2 diabetes examined on two occasions, an association was found between the decline in C‐peptide levels over time and the increase in plasma adiponectin 26 . Although there are many differences between type 1 and type 2 diabetes, including high levels of adiponectin in type 1 diabetes 14–17 and low levels in type 2 diabetes, 8 these results are in agreement with the idea of endogenous insulin secretion modifying adiponectin levels.…”
Section: Discussionmentioning
confidence: 52%
“…upregulation of surface RAGE expression (only marginally), secretion of inflammatory cytokines, and induction of apoptosis. The physiological serum concentration of GEs is usually less than 1 µg/ml [19], but higher levels of AGEs have been observed in diabetic patients [20]. It will be important for future studies to assess the extent to which our present results can explain the actual roles of basophils in disease conditions.…”
Section: Discussionmentioning
confidence: 96%
“…Higher plasma adiponectin concentrations in healthy and type 2 diabetic subjects in Western and Asian countries, including Japan, have been shown to be associated with lower fasting glucose, triacylglycerol, total cholesterol and low-density lipoprotein-cholesterol concentrations, and higher high-density lipoprotein (HDL)-cholesterol concentrations (18)(19)(20)(21)(22)(23). In addition, it has been reported that insulin resistance and hyperglycemia in people with diabetes are associated with elevated plasma protein levels of circulating inflammatory cytokines such as interleukin (IL)-1 ␤ , IL-6, IL-12, IL-18 and tumor necrosis factor (TNF)-␣ ( 24 -26 ).…”
mentioning
confidence: 99%